E-AGRAR PLATFORM: ASSESSMENT OF BENEFITS AND USAGE CHALLENGES FROM THE PERSPECTIVE OF BEEKEEPERS IN SERBIA - Bekić Šarić, Bojana; Paraušić, Vesna; Nastić, Lana (Journal of Agricultural Sciences (Belgrade), 2025)
The aim of the research is to understand beekeepers’ attitudes towards usefulness and usage challenges of the new government’s electronic service in agriculture - eAgrar. This service was launched in 2023 by the Ministry of Agriculture, Forestry and Water Management of the Republic of Serbia and the participation in this platform is mandatory for agricultural producers who want to be in the national subsidy system. Data for the purpose of this paper were collected during 2023, by using a structured online questionnaire. The number of respondents was representative (459), while purposeful random sampling ensured anonymity and credibility. Data processing included the application of descriptive statistics, χ2 test of independence, and Word Cloud tool. The majority of respondents (81.0%) think that they will benefit from the introduction of this platform, as it will make all administrative procedures faster, easier, and cheaper. For 64.7% beekeepers the platform is easy to use. About one-third of them find it somewhat challenging to use and rely significantly on the support of agricultural extension officers. Also, there is a statistically significant positive correlation only between the respondents’ level of education and level of difficulties in using the eAgrar platform. The results of this study are expected to provide agricultural policymakers in Serbia with insights into different aspects of the practical application of the eAgrar platform and also contribute to enriching the scientific knowledge about the application of new technologies in agriculture.